Urdū kī maʿrūf ẖvātīn afsānah nigār - Nainī, Asmāʾ (ʿAršiyah Pablīkešanz, 2017)
Study on the works of selected 20th century women Urdu novelists
Der Paralleltitel ist eine Umschrift von dem hinteren Buchumschlag
Keywords: Urdu fiction